The Influence of School Principal Leadership on Teacher Work Motivation in Elementary Schools - Solekha, Siti; Sumarno, Sumarno; Rasiman, Rasiman (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the influence of school principal leadership on the work motivation of elementary school teachers in the Sarwas 3 area of Pemalang District. Principal leadership plays a strategic role in fostering a positive work climate that enhances teachers’ enthusiasm and commitment. Employing a quantitative correlational approach, this research involved 130 teachers selected through proportional random sampling to ensure representative data. Data were gathered using Likert-scale questionnaires that captured teachers’ perceptions of principal leadership and their work motivation. Simple linear regression analysis using SPSS revealed that principal leadership significantly contributes to teacher motivation, accounting for 61.2% of its variance. The dominant leadership dimensions influencing motivation include interpersonal relations and collaborative decision-making. These results highlight that effective leadership fosters mutual trust and supportive relationships between principals and teachers. The study recommends enhancing strategic leadership competencies among principals, particularly in interpersonal communication and participative leadership, as a means to sustain teacher motivation. This study contributes to the literature by reinforcing the pivotal role of principal leadership in shaping teacher motivation and offers new insights into the integration of interpersonal leadership practices within the context of educational management in elementary schools.